Pelatihan Aplikasi Perkantoran Bagi Masyarakat Kelurahan Sidorejo - Nasution, Marnis; Akbar Ritonga, Ali; Rohani, Rohani; Bangun, Budianto; Ahmad Habibullah, Imam (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2023)
Village is a community unit that has territorial boundaries that has the authority to take care of all the interests of residents or the local community. The village is led by the Village Head who is assisted by village officials and supervised by the Village Consultative Body in accordance with Permendagri number 110/2016 regarding the duties and functions of the BPD. The lack of knowledge of residents about Information Technology such as the operation of Microsoft word and excel in terms of writing correspondence is an obstacle in their activities, especially for high school/vocational school level students or office workers. The aim of this Microsoft word and microwoft excel training is to improve the quality of Human Resources ( HR) for the people of Sidorejo Village, Labuhanbatu Regency. The methods in this training are the discussion method and the practical method. The results of this training show that there is an increase in the skills of the residents of Sidorejo Village, Labuhanbatu Regency in operating and using Microsoft Word and Microsoft Excel, this can help smooth their daily work and increase residents' knowledge about science and technology